Melacak Pemikiran Anthony Giddens Tentang Nation-State dan Modernitas - Nanang Indra Kurniawan (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2001)
This work is an analysis of Giddens's thinking on nation-state. It is a discussion of correlation between state, society and modernity. Modernity, in his analysis on nation-state, is placed as the important stand point for the understanding. Modernity itself has four institutional dimensions: heightened surveillance, capitalistic enterprise, industrial production and consolidation of centralized control of the means of violence. None is wholly reducible to any of the others. Two key questions will be answered by this study. First, what is modernity? How does it work? Second, what is nation-state?Whatapproach did Giddens use for analyzing nation-state? How does nation-state work in the frame of modernity? This work tries to answer all questions above. It is addresses to explore historical problematical reasons of his study on nation-state and then describe its characteristics. The most important thing, it is intended to analyse relationship between state, society and modernity in the development of nation-state.